NALAR FIQH REALITAS AL-QARADHAWI (Mendudukkan Relasi Teks dan Realitas Sosial) - MOHAMMAD MUFID (Syariah: Jurnal Hukum dan Pemikiran, 2014)
According to Islamic Jurist Ulema, the relationship between religion and social to determines Islamic law is a very interesting topic. Therefore, understanding the Qur'an nash and knowing the real situation would make it easier to determines the Islamic law. It is because impossible to understand the law if people do not understand the meaning of the text, social and some other causes. There is nash states that "the law can be changed according to the time and the place". It shows that looking at the reality is also important to the Islamic Sharia. Besides, Ijtihad also should see some of the realities and understand its nash and utilization correctly nowadays. This paper will describes some changes that have to be understood by Islamic jurist while learning the "Fiqh al-Waqi" from some doctor Yusuf Qaradawis comprehensions and some existing nash in Indonesia.